Contribuições a uma proposta de formação de inteireza do professor de matemática na perspectiva da complexidade - Dornelles, Marcia Iara da Costa (2013)
The investigation on the teacher s formation represents an opportunity to consider the kind of professional that is sent to the labor market. This reality is even more instigating when it becomes about the formation of Brazilian Mathematics teacher, because this is a course which is tensioned between the heritage of Cartesian linear thinking and the emergence of other paradigms that look at the human being and the world in a whole way. This research discusses the formation of the Mathematics teacher s wholeness in the perspective of the complexity. It started with the question: How are developed the subjective dimensions of the human being, such as the social, emotional and spiritual ones, at the course of Mathematics teacher formation, in the meaning of the wholeness of the being and of a future performance orientated by the transdisciplinary relationship with other areas of knowledge? The question evoked as a general goal the enlargement of the discussion about the Mathematics teacher s formation in the sense of the wholeness of the being in the perspective of the complexity theory. This is an interpretative descriptive qualitative research, based on Turato (2010).The composition is set on Morin ideas (2007, 2008) about the complex thinking; on Catanante (2000) about the human being characteristics; on the concept of wholeness of the being from Portal (2006); on Machado (2008) and on D Ambrósio (1997) about the Mathematics teaching; and finally on Imbernón (2011), about teacher formation. The investigation field is composed by three courses of Mathematics at the state of Rio Grande do Sul, in the internal attendance mode. The criteria used to choose the course was those who had grade five on ENADE exam on 2008. The interviewed subjects were the coordinator and two professors in each course, indicated by the coordinator. One of the subjects was from the exact science and the other had performances on methodological or practical subjects. To the data collection, it was used the half-structuredinterview, observation and field diary. The data analysis was based on Moraes e Galiazzi (2007).The understanding obtained by the interpretation of the findings points out that the interviewees (that were called Illuminators) recognize the presence of the rational, social and even the emotional dimensions, but that they react careful about the spiritual dimension, although they recognize it as a constitutive part of each person s subjectivity. They realize the need to innovate at this formation as one of the possible solutions to improve or minimize the failure on Mathematics teaching . They identify at the continued education a possibility to complete the human being in permanent become. With this recognition, I point out some indicators that contribute to rethink the Mathematics teacher formation: Enlargement of the dialogue between the teacher and his colleagues, breaking up the frontiers of scientific isolation, development of the work on other sciences interfaces.The education in the perspective of complex thinking demands a transdisciplinary attitude that helps the decision making in front of the problems that humankind faces. The development of innovative teaching proposals in which, besides the interdisciplinary relations, it is possible to contemplate the presence of the subjective dimensions of the human being. The prioritization of teaching strategies, conducted to interventions in the complex reality of life, that stimulate the curiosity, the creativity and that allow the Mathematics student to have success in the learning process and to be happy. The enlargement of the conscience of future teachers possibly will happen with the development of the subjective dimensions in spiritual, emotional and social contexts, in the sense of the wholeness of the being in the complexity perspective